Electrocardiographic nature of restored sinus rhythm after Cox maze procedure in patients with chronic atrial fibrillation who also had other cardiac surgery. (January 1997) - Kamata, J.; Nakai, K.; Chiba, N.; Hosokawa, S.; Sato, Y.; Nasu, M.; Sasaki, T.; Kitahara, H.; Izumoto, H.; Yagi, Y.; Itoh, C.; Hiramori, K.; et al.
Abstract : OBJECTIVE: To characterise heart rate variability and high frequency components of restored sinus rhythm after the maze procedure. The maze procedure for chronic atrial fibrillation may prevent thrombotic events and improve the quality of life. However, the electrocardiographic nature of restored sinus rhythm after the maze procedure has not been fully elucidated. PATIENTS AND METHODS: Between March 1993 and August 1995, 104 consecutive patients undergoing the maze procedure in combination with other cardiac surgery were studied. There were 100 long-term survivors (78 with mitral valve disease, 9 with aortic valve disease, 8 with congenital heart disease, and 5 others). Twenty age-matched patients with mitral valve disease who were in normal sinus rhythm preoperatively were enrolled as a control group. 30 days after surgery, the presence of arrhythmias and the circadian changes of heart rate variability were estimated by ambulatory electrocardiographic monitoring and the filtered P duration was evaluated by signal-averaged electrocardiogram. RESULTS: Restoration of sinus rhythm was observed in 73 of 100 cases. Subjects were classified into three groups according to their postoperative ambulatory electro-cardiographic monitoring findings: patients in group 1 (n = 73) (1a: 58 regular sinus rhythm; 1b: 15 sinus rhythm with frequent premature atrial contractions (> 1000/day); patients in group 2 (n = 21) still had persistent atrial fibrillation; and patients in group 3 (n = 6) required permanent pacemaker implantation because of sick sinus syndrome. The success rate of restoration of sinus rhythm was 88.3% if left atrial diameter was small (< 65 mm). Circadian changes in the low frequency to high frequency power ratio in group 1a were significantly diminished compared with control group (P < 0.01). Furthermore, the filtered P duration in group 1a (150 (20) ms) and group 1b (158 (23) ms) were longer than in the control group (122 (11) ms) (P < 0.01). CONCLUSIONS: The maze procedure may result in a decreased sinus response and non-uniform transmission of impulses in the atrium.